The Effect Of Group Activity Therapysocialization (Taks) Towards Reducing Loneliness In The Elderly At The Upt Of Elderly Social Services In The Social Services Of Binjai, North Sumatra Province In 2021 - Samfriati Sinurat; Lindawati F.Tampubolon; Evlin Nurani Zalukhu (Sean Institute, 2022)
Introduction: The aging process experienced by the elderly will cause a decrease in normal psychological, biological, spiritual, social and economic functions.The most common psychological problem in the elderly is the feeling of loneliness. Loneliness is a person's psychological state of the situation being faced, where a person always feels unnotified by the people around him and tends to be alone and never satisfied with what has been given by his surroundings. One way to overcome feelings of loneliness in the elderly is to provide socialization group activity therapy (TAKS). The purpose of this study was to determine the effect of socialization group activity therapy (TAKS) on reducing loneliness in the elderly at UPT social services for the elderlysocial services Binjai, North Sumatra Province in 2021.Methods : This type of research is pre-experimental with a one-group pre-post test design. The number of samples is 20 people with purposive sampling technique. The research instrument used a questionnaire and data analysis using the paired t-test.Results: The results of the study showed that 85% and severe feelings of loneliness in the elderly were 85% before receiving socialization group activity therapy (TAKS) and 10% mild loneliness in the elderly after receiving socialization group activity therapy (TAKS). The paired t-test result was 0.001 (p-value <0.05)Conclution : indicating that there was an effect of socialization group activity therapy on reducing loneliness in the elderly at the UPT for elderly social services, Binjai social service, North Sumatra province.